Proposed Model for Assessing CSF of Crisis Management Team: Scientific Committee for COVID-19 as a model (during 2020/2021) - Dekhakhni, wahiba; Mahboub, yamina (Finance and Business Economies Review, 2022)
The study aims to assess the role of the national committee for monitoring and following up on the COVID-19 virus in managing Algeria’s epidemiological crisis. A model of critical success factors consisting of five elements has been proposed and four outcomes. The coronavirus statistics were relied on during 2020 and 2021, The study concluded that the Scientific Committee’s team for monitoring and following up on the coronavirus crisis has the critical success factors to manage the crisis. The committee was able to develop potential and achieve satisfactory results. The study recommended the need to improve the quality of health services provided to citizens